Design of cyclic peptides with biological activities from biologically active peptides: the case of peptide modulators of melanocortin receptors. Issue 6 (November 2016) - Hruby, Victor J.
Abstract: Design of biologically active peptides is of critical importance for the development of potent, selective, nontoxic bioavailable drugs. A major approach that has been developed to accomplish this is the development of methods for the design and synthesis of a wide variety of cyclic peptides and peptidomimetics. In this short and general review, we outline the methods that have been developed for cyclization of peptides and how these have been used for peptide and peptidomimetic design using the melanotropin peptides and melanocortin receptors MC1R, MC3R, MC4R, and MC5R to illustrate aspects of this approach.